5x-5=3x-9

Simple and best practice solution for 5x-5=3x-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-5=3x-9 equation:


Simplifying
5x + -5 = 3x + -9

Reorder the terms:
-5 + 5x = 3x + -9

Reorder the terms:
-5 + 5x = -9 + 3x

Solving
-5 + 5x = -9 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-5 + 5x + -3x = -9 + 3x + -3x

Combine like terms: 5x + -3x = 2x
-5 + 2x = -9 + 3x + -3x

Combine like terms: 3x + -3x = 0
-5 + 2x = -9 + 0
-5 + 2x = -9

Add '5' to each side of the equation.
-5 + 5 + 2x = -9 + 5

Combine like terms: -5 + 5 = 0
0 + 2x = -9 + 5
2x = -9 + 5

Combine like terms: -9 + 5 = -4
2x = -4

Divide each side by '2'.
x = -2

Simplifying
x = -2

 

See similar equations:

| 7x-4=20+3x | | 5.3x-5.36=4.24-6.7x | | 6x=2-10 | | 2(y-3)=4y+6 | | a+8+-2(a+-12)=0 | | 12+10w=8w+6y | | X+(X*.11)=100 | | 12+10w=8w+64 | | 3x+3=6x | | 12x+-3x+11=4x+17+-9x | | 5x+-7=28 | | x-1=-9 | | c-5=6 | | 7=5u-43 | | -6y+14+4y=32 | | 5x+20=9x | | 1x(7-x)=8 | | x(7-x)=8 | | 34=17-(x-5) | | 7x+-1x=8 | | 58+8=23 | | 5x+8=23 | | (X-1)(x+1)(2x-5)=0 | | 5(x-3)=10 | | 4(5+3x)=14 | | -2(x-3)+6=4x | | 2(x-4)-6(2x-3)=0 | | 5x=2x+9 | | 7(2d-1)+5(2-3d)=2d | | 2x+2y=5x+9 | | 6(2n-5)=-3(7-3n) | | -40=7-6s | | 12w+40=200 | | 4w+5z=16 | | 42+8x+13=7 | | -3=x+x+x | | 5(x+3)-2(x-1)=20 | | 10p-3(5+2p)= | | x=9+8 | | -2(5x-3y+10)= | | 3.4t+19.36=-10.22 | | -5=1-2p | | 7=5(x-4)+2 | | 6(2+y)-4=-10 | | 4.6b+26.8=50.72 | | -2(10)= | | 3(p-4)=12 | | 4x+2=2x-4 | | -2(6+p)=8 | | 5(z-1)=5z | | 3(x-4)=4(2x+3) | | T+4(1-t)=9t | | -12=4-2(x+3) | | 2x+6=4x | | 2m=6-5m | | 6-5m=2m | | 3(b-2)-4(2b+5)=9 | | (3m-5)(q+4)2p(4-6n)=0 | | 18=2(g+4)+3(2g-6) | | -12=4-2(x-3) | | 2.06d+18=10.84 | | 4x-2=22 | | -3=5r+7 | | 7(y-2)+8=3(y-4)-2 | | 4(x+2)=48 |